Knowledge and attitudes of medical students regarding human papilloma virus infection and vaccine: cross-sectional study from Jordan - Taha, Hana; Alhawamdeh, Taher; Alkhaldi, Sireen M.; Ali Albsoul, Rania; Al-Ani, Abdallah; Awamleh, Suhib; Al-Maayeh, Amin Y.; Qaqish, Arwa; Mahmoud, Ameen; Abu-Surrah, Diana; Berggren, Vanja (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundAs of the present moment, Jordan is yet to incorporate cervical cancer screening in its cancer control program nor advocates for vaccines. This paper aims to examines the perceptions and attitudes of medical students towards HPV and its vaccine.MethodsWe conducted a cross-examination of HPV knowledge and vaccine uptake among medical students across the period between January and March 2024. Participants completed a questionnaire developed and validated by the existing literature. The questionnaire was composed of 4 domains pertaining to sociodemographic, knowledge of HPV, knowledge of HPV vaccine, and attitudes. Medical students were conveniently sampled from Jordan’s six public medical schools. Predictors to self-vaccinate, recommending vaccination to friends/family, and recommending vaccination to patients were examined using a binary logistic regression model. All analyses were conducted on R version (4.3.3).ResultsA total of 473 medical students were included in the final analysis. On a scale of 12 and 8, mean HPV and vaccine knowledge scores were 5.4 ± 3.1 and 2.9 ± 1.9, respectively. Knowledge of HPV and its vaccine were significantly higher among females, students in their clinical years, and those with self-perceived understanding of HPV (all p <0.05). Intention to self-vaccinate against HPV was predicted by higher HPV and vaccine knowledge scores. Male participants were significantly less likely to self-vaccinate compared to females (OR: 0.61; 95%CI: 0.40 – 0.91). Similarly, higher HPV and vaccine knowledge scores were associated a higher likelihood to recommend the vaccine to family or patients. On the other hand, male participants were significantly less likely to recommend the vaccine to patients compared to their female counterparts (OR: 0.62; 95%CI: 0.40 – 0.95).ConclusionThe study implies that the overall awareness and attitudes regarding HPV and its vaccine is alarmingly poor among medical students. Moreover, there exists a gender difference in the knowledge and attitudes favoring females. Concerned policy makers and institutions should strive to improve vaccine awareness and uptake through informational, behavioral, and environmental interventions. Moreover, medical students should be well equipped to tackle HPV vaccine hesitancy through curricular reforms, targeted training, and increased exposure to public vaccine promotional efforts.